Multi-chord observation of stellar occultation by the near-Earth asteroid (3200) Phaethon on 2021 October 3 (UTC) with very high accuracy. (20th December 2022) - Yoshida, Fumi; Hayamizu, Tsutomu; Miyashita, Kazuhisa; Watanabe, Hiroyuki; Yamamura, Hidehito; Akitaya, Hiroshi; Asai, Akira; Fujiwara, Yasunori; Goto, Tateki; Hashimoto, George L; Hatanaka, Akitoshi; Horaguchi, Toshihiro; et al.
Abstract: We observed a stellar occultation by (3200) Phaethon, which occurred in western Japan on 2021 October 3 (UTC). This observation was requested by the DESTINY + mission team, which plans to conduct a flyby of asteroid Phaethon in 2028. Overall, this research effort contributes towards a large-scale observation campaign with a total of 72 observers observing from western Japan to southern Korea. 36 stations were established, and stellar occultation by the asteroid Phaethon was detected in 18 of them. This is the first time that this many multiple chord observations have been made for such a small asteroid (it has a diameter of 5–6 km). Observational reductions show that the apparent cross-section of Phaethon at the time of the occultation could be approximated using an ellipse with a major diameter of 6.12 ± 0.07 km and a minor diameter of 4.14 ± 0.07 km, and a position angle of 117.°4 ± 1.°5. As can be seen from the small error bars of the fitted ellipse, we have succeeded in estimating the shape and size of the asteroid with an extremely high degree of accuracy. Our observation results, together with other observations, will be used to create a 3D model of Phaethon and to improve its orbit. The instruments that we used for this observation are commonly used by many amateur astronomers in Japan for occultation observations and are not difficult to obtain. This paper describes the method and results of our observations using a CMOS camera and a GPS module, so that many people can participate in occultation observations in the future.